2013
DOI: 10.1186/1471-2474-14-226
|View full text |Cite
|
Sign up to set email alerts
|

Computer work and self-reported variables on anthropometrics, computer usage, work ability, productivity, pain, and physical activity

Abstract: BackgroundComputer users often report musculoskeletal complaints and pain in the upper extremities and the neck-shoulder region. However, recent epidemiological studies do not report a relationship between the extent of computer use and work-related musculoskeletal disorders (WMSD).The aim of this study was to conduct an explorative analysis on short and long-term pain complaints and work-related variables in a cohort of Danish computer users.MethodsA structured web-based questionnaire including questions rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 50 publications
4
43
2
9
Order By: Relevance
“…While on the other hand their physical activity has decreased, resulting in musculoskeletal problems. [30] According to the data of the present study, students' median age in both groups ranged from 15 to 16 years and the majority of Saudi teenagers were males (82.8%) while females participated 59.1% in Egyptian teenage. Regarding using the internet, academic achievement was 37.7%, social communication (60.7%) and entertainment (66.5%) in both groups.…”
Section: Discussionmentioning
confidence: 63%
“…While on the other hand their physical activity has decreased, resulting in musculoskeletal problems. [30] According to the data of the present study, students' median age in both groups ranged from 15 to 16 years and the majority of Saudi teenagers were males (82.8%) while females participated 59.1% in Egyptian teenage. Regarding using the internet, academic achievement was 37.7%, social communication (60.7%) and entertainment (66.5%) in both groups.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have already identified gender differences in pressure sensitivity (Chesterton et al, 2003;Camargo et al, 2009;Palmeira et al, 2011). Biological and biosocial mechanisms including gonadal hormones, genetic factors, and multiple psychological aspects are suggested as factors explaining gender differences in pain sensitivity (Madeleine et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…This entails that our findings must be inter-Social support at work, forward bending, and low-back pain problems are more likely to report certain psychosocial exposures than healthy workers (58). For example, if a worker experiences a low level of social support at work, this may induce a higher pain report compared to workers experiencing high levels of social support.…”
Section: Strengths and Limitationsmentioning
confidence: 99%